Responsive Evaluation in the Interference Zone Between System and Lifeworld. (December 2017) - Abma, Tineke A.; Leyerzapf, Hannah; Landeweer, Elleke
Responsive evaluation honors democratic and participatory values and intends to foster dialogues among stakeholders to include their voices and enhance mutual understandings. The question explored in this article is whether and how responsive evaluation can offer a platform for moral learning ( Bildung ) in the interference zone between system and lifeworld. A case example from Dutch psychiatry is presented. Policy makers aimed to develop a "monitoring instrument" for closed psychiatric wards to protect patient rights and prevent incidents. Tensions arose between strategic action and system values (accountability, efficiency, control, safety) and the search for meaning and morality. Several dynamics were set in motion. Through the creation of communicative spaces in which there was room for expression of emotions and stories, the "colonization" by system values was countered. Another dynamic called "culturalization" started simultaneously, that is, adoption of lifeworld values in the system world, which resulted in constructive dialogues on the meaning of good care and moral learning.